Leadership Communication and Employee Motivation : a Case Study of CV Utama - Witama, Susan; Yunita Wono, Hilda (Jurnal Spektrum Komunikasi, 2024)
Communication within the company is the most important thing, the better the communication you have, the easier it will be to achieve company goals. To achieve good communication, a leadership communication strategy is needed within the company. Leadership communication is important both for making decisions and managing risks. Communication strategy One of the largest distribution companies in Surabaya is CV Utama which focuses on the distribution of household equipment. Company leaders have an important role in creating good communication between employees and motivating them to work well. CV Utama has received several awards for their success in working with the factories from which they order goods. The aim of the research is to determine leadership communication strategies in increasing employee motivation. This research uses a quasi-qualitative method to collect data from interview results with prepared questions which are based on existing theories, also reinforced with documentation in the form of documents or images and developed to obtain the results of leadership communication strategies in increasing employee work motivation at CV Utama. The research results indicate that CV Utama has implemented leadership strategies effectively. They have a good leadership system for assigning tasks to employees. Employees are highly motivated due to the sense of camaraderie and good communication among them. Therefore CV Utama has implemented good leadership strategies in the company. However, they still have a weakness in the morning system for the next generation to ensure consistency and a well-documented system.